Molecular identification of indigenous arbuscular mycorrhizal fungi in the rhizosphere of black pepper (Piper nigrum) in West Lampung, Indonesia - RAHMAT HIDAYAT; MARIA VIVA RINI; RUSDI EVIZAL; AGUS KARYANTO; PAUL BENYAMIN TIMOTIWU; SALWA AZZAHRA (Society for Indonesian Biodiversity, 2026)
Abstract. Hidayat R, Rini MV, Evizal R, Karyanto A, Timotiwu PB, Azzahra S. 2026. Molecular identification of indigenous arbuscular mycorrhizal fungi in the rhizosphere of black pepper (Piper nigrum) in West Lampung, Indonesia. Biodiversitas 27 (5): d270526. https://doi.org/10.13057/biodiv/d270526. Black pepper (Piper nigrum) serves as a vital economic spice commodity in Indonesia, yet its agricultural productivity is frequently constrained by suboptimal soil conditions, particularly in acidic marginal drylands. The use of indigenous Arbuscular Mycorrhizal Fungi (AMF) offers a sustainable, environmentally friendly strategy to mitigate these abiotic stresses. However, the specific diversity of AMF communities in the black pepper plantations of West Lampung remains largely underexplored. Therefore, this study aimed to conduct a species-level molecular identification of indigenous AMF isolated from the black pepper rhizosphere in this region. Five distinct spore isolates were successfully recovered using a trap culture method and were initially characterized based on morphological attributes. For accurate taxonomic resolution, molecular analysis was performed using nested Polymerase Chain Reaction (PCR) targeting the 18S Small Subunit (SSU) rRNA gene with AML1/AML2 primers. This was followed by DNA sequencing and phylogenetic reconstruction using the Neighbor-Joining method. The phylogenetic analysis confirmed the presence of four distinct evolutionary lineages: Ambispora leptoticha (SP1), Acaulospora cf. spinosa (SP2), Acaulospora colombiana (SP4), and unclassified Glomeromycotina sp. (SP3 and SP5). Interestingly, the typically ubiquitous genus Glomus was entirely absent from the analyzed isolates, while the sampled soil exhibited extreme acidity (pH 4.13) and unexpectedly high available phosphorus (77.17 ppm). This study provides a crucial molecular baseline for indigenous AMF, confirms the first molecular record of the Ambispora lineage, and supports the future development of site-specific bioinoculants tailored for acidic soils.